Aggregation-Free Process for Functional CdSe/CdS Core/Shell Quantum Dots - Moon, Jihyung; Choi, Kyu-Sil; Kim, Byungjoo; Yoon, Kwon-Ha; Seong, Tae-Yeon; Woo, Kyoungja (American Chemical Society, 2009)
Particle aggregation is implicated in a preparation of water-soluble functional nanoparticles and there is currently great interest in aggregation-free and water-soluble nanoparticles with a specific functionality. In this report, we present the aggregation-free surface modification process that provides water-soluble and functional quantum dots below 10 nm in hydrodynamic diameter. Our strategy is based on the reasoning that particle aggregation occurs due to polychelating internanoparticle hydrogen bonding interactions through surface molecules when they are no longer ionized. Therefore, the very strategy is to interrupt internanoparticle hydrogen bonding interactions by placing long chain hydrocarbon pillars (mercaptoundecanoic acid) which are bonded to functional molecules (folic acid or polyethylene glycol derivative) at appropriate distances on the CdSe/CdS core/shell quantum dots (QDs). The remaining QD surface area is then replaced by short-chain hydrophilic molecules (mercaptopropionic acid) endowing water solubility. However, the internanoparticle hydrogen bonding interactions, thereby resulting in aggregation, are inhibited by the steric hindrance of the already present bulky functional molecules. The current process showed an applicable feasibility for superparamagnetic iron oxide nanoparticles, too.
Keywords: NANOCRYSTALS; CDTE; WATER; LUMINESCENT; LIGANDS; NANOPARTICLES